Comparative risk-benefit profiles of different femoral drilling techniques in anterior cruciate ligament reconstruction: A protocol for a systematic review and network meta-analysis. Issue 23 (5th June 2020) - Wang, Ning; Zhu, Zhenglei; Wu, Ziying; He, Hongyi; Wang, Haochen; Li, Wei; Xie, Dongxing; Wang, Yilun
Abstract: Background: Anterior cruciate ligament (ACL) injury experiences about 200, 000 isolated cases annually, and ACL reconstruction has become the gold standard for the restoration of stability and functionality. In view of that incorrect graft placement is a common cause of ACL reconstruction failure, it is critically important to ensure that the tibial and femoral tunnels are properly placed during the operation. Therefore, we intend to conduct a network meta-analysis to comparatively evaluate the clinical outcomes among the different surgical techniques in ACL reconstruction. Methods: Embase, PubMed, and Cochrane Library will be searched through to retrieve the relevant literature up to April 2020. The outcomes include the International Knee Documentation Committee subjective/objective score, Lachman test, Lysholm score, laxity of knee joint, pivot-shift test, Tegner activity scale, and the number of adverse events. A Bayesian hierarchical framework will be used to evaluate the comparative efficacy among different fixation devices. Cochrane Q test and I 2 statistics will be applied to evaluate the heterogeneity, and the Cochrane risk of bias assessment tool will be employed to evaluate the study quality and the risk of bias. Results: The comparative risk-benefit profiles of different femoral drilling techniques will be evaluated based on the existing evidence, in order to summarize a prioritization regimen. Conclusion: Findings from this network meta-analysis will provide useful reference to patients, surgeons, and guideline makers in the related fields. Registration: Open Science Framework (OSF) Preregistration. April 20, 2020. osf.io/uzahs